2016
DOI: 10.18632/oncotarget.12666
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab and wound-healing complications: a systematic review and meta-analysis of randomized controlled trials

Abstract: A meta-analysis was conducted to estimate the risk of wound-healing complications in patients who treated with neoadjuvant-adjuvant bevacizumab in various oncological indications. We searched PUBMED, EMBASE and the Cochrane Library through June 2016 to identify randomized controlled trials of bevacizumab and wound-healing complications. Seven RCTs studies involving 5,147 participants were included in the analysis. Compared with routine therapy, bevacizumab increased the incidence of wound-healing complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…In the sample presented in this paper, it is noteworthy that immunization with CIGB-247 was safe and well tolerated in all these cases. In addition to this experimental evidence, a detectable VEGF-specific patients [54]. These clinical observations with CIGB-247 could be explained by the incomplete abrogation of platelet VEGF levels after immunization with CIGB-247 [55].…”
Section: Discussionmentioning
confidence: 92%
“…In the sample presented in this paper, it is noteworthy that immunization with CIGB-247 was safe and well tolerated in all these cases. In addition to this experimental evidence, a detectable VEGF-specific patients [54]. These clinical observations with CIGB-247 could be explained by the incomplete abrogation of platelet VEGF levels after immunization with CIGB-247 [55].…”
Section: Discussionmentioning
confidence: 92%
“…The results of our study indicated that bevacizumab extended the time required for absorption of the hyphema from the anterior chamber. Bevacizumab use is known to cause wound healing complications (12); therefore, we believe that the extended duration required for hyphema resorption was due to disruption of the wound healing process. In a normal wound, the blood turns into a clot during the healing process.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, two individuals included in our present study were submitted to major urgent surgeries during immunization with CIGB-247 without reports of wound healing impairment. It is know that bevacizumab treatment increases the risk of bleeding and wound healing complications in cancer patients [54]. These clinical observations with CIGB-247 could be explained by the incomplete abrogation of platelet VEGF levels after immunization with CIGB-247 [55].…”
Section: Safety Profile and Immunogenicity Of Cigb-247 In Patients Wimentioning
confidence: 99%